Is There a Differeance Performance Between Industry Base Smes in The Sarbagita Bali ? : A Comparative Approach - Ni Nyoman Yuliarmi; Ni Putu Martini Dewi; Surya Dewi Rustariyuni (PT. Publikasiku Academic Solution, 2023)
This study seeks to: 1) analyze differences in social capital, human resources, and financing sources of small and medium enterprises (SMEs) based on the industry in the Sarbagita Area, Bali Province; 2) analyze performance differences among SMEs based on the industry in the Sarbagita Area, Bali Province. By using a location-stratified random sampling technique to determine the number of samples and accidental sampling to determine respondents, this study used 203 SME business units. We used both primary and secondary data sources to generate quantitative and qualitative data. Data was ge rated by non-behavior observations, structured interviews, and in-depth interviews. The study then analyzed the data using the ANOVA analysis. The results show that: 1) the manufacturing and trade industries have different social capital; there is a difference in human resources between the trade and service Industries; the manufacturing and service industries have different financing sources, especially for internal financing sources while other financing sources do not exhibit different significant difference; 2) SMEs in the manufacturing and trade industries have different performance. Based on the results, this study suggests that: 1) SMEs need to rely on not only internal financing sources because external financing is sufficiently available with affordable interest rates; 2) SME owners need to enhance their networks with their fellow entrepreneurs or with their suppliers to improve their business performance.